'Get me out of this dream!': making a therapeutic alliance and working in the transference with a psychotic adolescent boy. Issue 1 (2nd January 2017) - Mirvis, Hillel
Abstract : This paper discusses the challenges of struggling to build and maintain a therapeutic alliance with a psychotic adolescent boy who did not share an allied perception of reality with his therapist, and who insisted that his therapist did not exist. The paper poses the question of whether, under such circumstances, it is ever appropriate or tolerable to make transference interpretations. Drawing on detailed clinical material, the author attempts to make sense of how it was possible to make some contact with his patient, given these technical difficulties.